A Lotus 1-2-3 macro system to analyze a cross of haploid individuals - D. Z. SKINNER; S. A. LEONG (Fungal Genetics Reports, 1990)
The use of RFLPs to construct saturated genetic maps results in the generation of very large sets of data. The management of these data, and the calculations needed to test for linkage relationships, is greatly facilitated by the use of an electronic spreadsheet on a personal computer. Using the spreadsheet Lotus 1-2-3TM (Lotus Development Corp., Cambridge, MA), we have found that the raw data can very efficiently be entered, viewed, edited, sorted, searched, and printed. We have written a program, utilizing Lotus 1-2-3 macro subcommands, that analyzes segregation data from a cross of haploid individuals in several ways